2002
DOI: 10.5014/ajot.56.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Standardized Instrument To Assess Computer Task Performance

Abstract: The Assessment of Computer Task Performance provides occupational therapists with an accurate test to measure computer performance and can assist them in providing computer access services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
1
22
0
5
Order By: Relevance
“…Table 3 provides the mean, minimum, maximum, and percentile scores for the ACTP subtests. The effect sizes provided in Figures 1 and 2 put the differences between this study sample's and the sample scores of Dumont et al (33) into perspective. The negligible to small effect sizes and the 95% CIs crossing zero suggest that this study sample's keyboarding speed scores were comparable to the nonimpaired sample of Dumont et al (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 provides the mean, minimum, maximum, and percentile scores for the ACTP subtests. The effect sizes provided in Figures 1 and 2 put the differences between this study sample's and the sample scores of Dumont et al (33) into perspective. The negligible to small effect sizes and the 95% CIs crossing zero suggest that this study sample's keyboarding speed scores were comparable to the nonimpaired sample of Dumont et al (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The HAQ data were transformed into an overall HAQ DI score (32). Dumont et al (33) only reported the time score for the second administration of each test. We therefore only used the time score from the second administration of each of our tests for data analyses.…”
Section: Impaired Hand Function and Computer Use Speed In Ra Patientsmentioning
confidence: 99%
See 3 more Smart Citations